Management of Christian Character Education Curriculum Based on Dormitory Abdi-Allah Theological College Trawas-Mojokerto - Thinna Naftali Woenardi; Haris Supratno; Mudjito (Indonesia Approach Education, 2022)
Abdi Theological College Trawas-Mojokerto or abbreviated as STTIAA Trawas, is a higher education institution that is engaged in preparing its graduates to become spiritual leaders in several churches. This research aims to understand and deepen the symptoms of a group of students at STTIAA Trawas related to their character while staying on campus. This is a social phenomenon as well as a problem related to the individual human being. Second, this research uses a theoretical framework that can shape or influence the study being researched. This research uses a qualitative design. Based on the research background, the research focus is generally stated: (1) The boarding-based Christian character education curriculum at Abdi-Allah Theological College Trawas-Mojokerto; and (2) The implementation strategy for the hostel-based Christian character education curriculum at the Abdi-Allah Theology College Trawas-Mojokerto. So that, the conclusions of this research remarks 1) The management of Christian character education curriculum that influences Dormitory Abdi Theological High School Trawas-Mojokerto are: Holiness (85.42% good), Love (82.17% good), and Commitment (71.83% good). Thus, the students’ lifestyle based on dormitory dominated by Holiness, Love, and Commitment is significant; 2) The management of Christian character education curriculum can affect the students’ lifestyle based on dormitory in which character transmission occurs without competition among group members as follows (a) Moral knowing, (b) Moral feeling, (c) Moral behavior.